LEGAL PROTECTION OF HOUSING CONSUMERS DUE TO DEVELOPER'S UNLAWFUL ACT IN BENTIRING VILLAGE, BENGKULU CITY - Emelia Kontesa (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Legal protection places an emphasis on the state or government fulfilling the obligations of the community. In the concept of legal protection, there is a demand for the right to legal protection to be fulfilled if the obligation for the law to fulfill the law is carried out, and there will be restrictions on the legal protection of a person who performs legal acts. Legal protection rests on and originates from the concept of the recognition and protection of human rights. This research is grouped in the humanities field if it is related to the RIP of Bengkulu University. It is very relevant to be examined in accordance with the development of the general principles of good governance, which together can be said to be the principles of good governance. The government must protect the interests of housing consumers who are in good faith because they have made house payments both in installments and in cash and have even obtained certificates of land rights. The final effort is a result of the Criminal Court decision, which states that the developer's unlawful actions have now reached the cassation level. If this decision is legally binding, it will result in the loss of land rights for consumers of Grand Korpri Bentiring housing because the land has become an asset of the Bengkulu city government. This research focuses on the consequences of the developer's unlawful act and his responsibility, as well as what efforts the government can make in relation to the protection of housing consumers. Similarly, the criminal acts committed by the developer should not be charged to consumers or result in the elimination of consumer land rights because the land falls to the state due to the proof of unlawful acts (PMH) from the developer. This is in accordance with the adage nemo punitur pro alieno delikto, which means that no one is punished for the actions of others. While civil law liability based on tort (onrechtmatige daad) is based on the existence of a legal relationship between housing consumers and developers through a sale and purchase agreement.